63.0k views
5 votes
2(4x - 6) = 6x - 4

A) 4
B) 8
C) -4
D) no solution

User Dscl
by
5.8k points

2 Answers

0 votes

2(4x - 6) = 6x - 4

First: Distribute

8x - 12 = 6x - 4

Second: Add -12 from both sides

-12 cancels out

-4 + -12 = -16

8x = 6x - 16

Third: Subtract 6x from both sides

6x cancels out

8 - 6 = 2

2x = -16

Finally: Divide 2 from both sides

2 cancels out

-16/2 = -4

Answer: -4

Hope this Helps!!


User TheLoneJoker
by
5.0k points
2 votes

The answer should be A) 4


User Runeks
by
6.2k points